The Effect of Intellectual Capital on Firm Value with Company Reputation and Financial Performance as Mediation Variables - Jao, Robert; Kampo, Kunradus; Holly, Anthony; Bakrie, Irene (Contemporary Journal on Business and Accounting, 2025)
Purpose – This research is aimed to determine the effect of intellectual capital on firm value with corporate reputation and financial performance as mediating variables. Design/methodology/approach – This research uses secondary data obtained by using documentation method. The data source in this research is the financial reports of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period and have score Corporate Image Index (CII) published by Frontier Consulting Group. The sample were selected using purposive sampling method, with a total sample of 39 data. Method used in this research is path analysis. Findings – The result of this research indicate that intellectual capital has a positive and significant effect on company reputation. Intellectual capital has a positive and significant effect on financial performance. Company reputation has a positive and significant effect on firm value. Financial performance has a positive and significant effect on firm value. Intellectual capital has a positive but not significant effect on firm value. Company reputation is able to mediate the effect of intellectual capital on firm value. Financial performance is able to mediate the effect of intellectual capital on firm value. Originality – This study integrates corporate reputation and financial performance as mediating variables in the relationship between intellectual capital and firm value, focusing on the banking sector in Indonesia that possesses a Corporate Image Index (CII) score. Keywords: Intellectual Capital, Firm Value, Company Reputation, Financial Performance Paper Type Research Result